PENGARUH PELATIHAN KERJA, KUALITAS KERJA DAN SEMANGAT KERJA TERHADAP PENGEMBANGAN KARIER PT. INDOMARCO PRISMATAMA, AREA, TAMAN, SIDOARJO - Martah, Varid (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2025)
This research aims to determine the influence of job training, work quality and work enthusiasm on career development at PT. Indomarco Prismatam area, Taman, Sidoarjo. The method used in this research is a quantitative method with a sample size of 100 respondents. The technique used in this research is a saturated sampling technique. The population in this study is the population of all employees in the Taman, Sidoarjo area. Therefore, the population size is the same as 100 samples. The independent variables in this research are job training, work quality and work enthusiasm with the dependent variable being career development. Data obtained using a questionnaire is related to job training, work quality and work enthusiasm for career development. The analysis technique used is multiple linear regression analysis, classical assumptions, t test, f test, and coefficient of determination test using the SPSS 22.0 for Windows program. The partial research results of job training, work quality and work enthusiasm have a positive and significant effect on career development. This can be seen from the calculated t value for job training of 7.987 > t table 2.578, the t calculated value for work quality 9.718 > t table 2.578, the calculated t value for work enthusiasm 4.914 > t table 2.578. The results of the f test obtained a calculated F value of 37.753 > F table 0.1957 with a significance level of 0.001. Thus, it can be concluded that simultaneously or together the variables of job training, work quality and work enthusiasm have a positive and significant effect on employee career development. From the results of the analysis, the R2 coefficient of determination value is 0.541, meaning that the independent variables of job training, work quality and work enthusiasm together contribute 62% to the dependent variable of career development.